Migration Governance from an Institutional Perspective: An Index for “Good” Migration Governance - Melike Aktaş Bozkurt; Hakan Karabacak; Yaşar Köse (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
The widespread socio-economic effects of migration make migration governance critical from an administrative and institutional perspective. Based on good governance principles, this article develops an Index for Good Migration Governance (IGMG). For this purpose, five principles of good governance (effectiveness, transparency, accountability, participation and legal framework) were selected. These principles are contained in documents published by the World Bank, the United Nations or the International Monetary Fund, which have made significant contributions to the development of good governance principles. The index is calculated using the methodology used by the European Commission in business and consumer surveys. Unlike the migration indexes developed in the past, IGMG builds on the selected principles of good governance from an institutional perspective and focuses on institutional structures related to migration governance. IGMG aims to raise the awareness of organizations on migration policies and practices and enable them to take the necessary steps for good migration governance.